2013
DOI: 10.3399/bjgp13x663046
|View full text |Cite
|
Sign up to set email alerts
|

Under-provision of medical care for vascular diseases for people with dementia in primary care: a cross-sectional review

Abstract: BackgroundVascular diseases contribute to the causation and progression of clinical dementia. AimTo evaluate the quality of medical care for vascular diseases provided to people with dementia, the patient and practice characteristics that influence quality, and to compare care with that provided to those without dementia. Design and settingObservational, cross-sectional review of primary care records of people with dementia from 52 general practices from five primary care trusts in the UK, and comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
(64 reference statements)
0
13
1
Order By: Relevance
“…Within the group who had dementia the most disadvantaged appeared to be women, individuals living in care homes and those with fewer comorbid physical conditions and medications (Connolly et al . ).…”
Section: The Role Of Social Class In Diagnosis and Treatmentmentioning
confidence: 99%
“…Within the group who had dementia the most disadvantaged appeared to be women, individuals living in care homes and those with fewer comorbid physical conditions and medications (Connolly et al . ).…”
Section: The Role Of Social Class In Diagnosis and Treatmentmentioning
confidence: 99%
“…Ten 98,110,117,118,129,136,139,145,155,161 of the 11 studies found some evidence that people with dementia were less likely to receive the same quality of care or access to services as those without dementia. For instance, studies found that people with dementia were less likely to receive monitoring for diabetes-related problems 97,136 and had reduced access to treatment such as intravenous thrombolysis for stroke, 129 surgery for cataracts, 110 treatment for age-related macular degeneration (AMD) 98,117 or services for diabetes.…”
Section: Comprehensiveness and Equitymentioning
confidence: 99%
“…Although heterogeneity in the populations and differences in the way that conditions were ascertained make comparisons across studies difficult, the data do suggest that the rate of diabetes in people with dementia may be between 13% and 20% and the rate of stroke may be between 16% and 29%. Of the 11 studies 98,110,117,118,123,129,136,139,145,155,161 that compared access to treatment or receipt of services in groups with and without dementia, 10 98,110,117,118,129,136,139,145,155,161 found some evidence that people with dementia were less likely to receive the same quality of care or access to services than those without dementia.…”
Section: Scoping Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 74 papers, 65 of which were classified as primary references [2,5,11,13, and nine as associated papers [84][85][86][87][88][89][90][91][92]. Study characteristics are summarised in the list below and details of individual studies, including the links between primary and associated papers, in Additional file 1.…”
Section: Description Of Studiesmentioning
confidence: 99%